Evaluating IGBT temperature evolution during short circuit operations using a TSEP-based method. (September 2019) - Ceccarelli, L.; Wu, R.; Iannuzzo, F.
Abstract: Thermal stress during abnormal events can severely affect the reliability of power semiconductor devices. This paper proposes a method to estimate the junction temperature Tj evolution of insulated-gate bipolar transistors (IGBTs) during short circuit (SC). After the extensive non-destructive SC characterization of a commercial discrete 1.2 kV/40 A IGBT device and a proper calibration procedure, the IGBT SC current ISC is proved to be a suitable temperature-sensitive electrical parameter (TSEP) for an accurate and fast Tj estimation. The method is easy to implement and shows promising performance for initial test temperature up to 150 °C. The Tj estimation method takes into account self-heating effects and the dependence on the collector-to-emitter voltage VCE in a wide range of operating conditions. The estimated temperature has shown good agreement with simulation results based on the finite-element analysis (FEM) of the chip geometry. The results indicate that Tj can be temporarily much higher than the datasheet maximum operating Tj, without catastrophic failures, which represents a considerable threat to the reliability of these devices. Highlights: The IGBT short-circuit current represents a suitable electrical parameter for a non-invasive junction temperature estimation; A calibration can be performed by mapping the current peak at different test temperatures and collector voltages; A 1.2-kV IGBT has been tested under 10-μs short circuit pulses up to 150 °C and 700 V to demonstrate the calibration; The calibration shows significant sensitivity and linearity, while the estimatied temperature matches FEM simulations.